1994
DOI: 10.1080/02652039409374258
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene terephthalate bottles (PRBs): A health and safety assessment

Abstract: As part of a multi-client project, the potential public health risks of the reuse of polyethylene terephthalate (PET) refillable bottles (PRBs) following possible misuse has been investigated. Participants in the project provided data and information from previous studies conducted independently at contract laboratories. These studies were sponsored by the clients in order to provide further research data on PET containers and their safety. In this report, the results of five of these studies along with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…E-mail: helene.widen@sik.se bottles (Feron et al 1994; Komolprasert and Lawson 1997;Tawfik et al 1997;Jetten et al 1999). The refillable bottles were exposed to chemical substances such as household chemicals, pesticides, automotive products, etc.…”
Section: Introductionmentioning
confidence: 98%
“…E-mail: helene.widen@sik.se bottles (Feron et al 1994; Komolprasert and Lawson 1997;Tawfik et al 1997;Jetten et al 1999). The refillable bottles were exposed to chemical substances such as household chemicals, pesticides, automotive products, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Because of their infragility, light weight, recyclability and processability, advantages of the glass bottle and the one way plastic bottle are combined when a returnable plastic bottle is considered. However, earlier studies have shown that certain chemical substances (pesticides, household chemicals) are absorbed by the plastic when bottles are misused by the consumer (1)(2)(3)(4)(5). Part of the chemical is retained by the plastic even after normal caustic washing and can migrate into the contents of a refilled bottle.…”
Section: Introductionmentioning
confidence: 95%
“…These substances may originate from a previous food product or result from consumer misuse. Toxicological evaluations of a wide range of consumer misuse products have indicated no risk to public health (Feron, Jetten, de Kruijf, & van den Berg, 1994;Tawfik, Devlieghere, Steurbaut, & Huyghebaert, 1997). However, the transfer of odour and flavour substances from a previous filling can lead to off-odours which change the organoleptic properties of the next beverage contained in a refillable bottle (Nielsen, 1994;Sto¨llman, 1995;Jetten, de Kruijf, & Castle, 1999) and may even result in consumer complaints (Wide´n, Leufve´n, & Nielsen, 2005).…”
Section: Introductionmentioning
confidence: 98%